Meneropong Dampak Stress, Social Skills dan Internet Addiction pada Office Workers semasa Covid-19 - Angela Novianti; Muhammad Rafi Akhyari; Syifa Nadhifah Hakim; Nopriadi Saputra (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: This study aimed to determine how much coping stress levels, social skills, and internet addiction affect employee engagement of millennial employees during the COVID-19 pandemic. Research Methodology: Questionnaires were distributed to 391 millennial office employees during the Covid-19 pandemic. The samples used were only 196 respondents because we used the Krejcie and Morgan method. The technique used by the author to analyze the data was multiple regression techniques. Results: This study show that social skills and internet addiction affect employee engagement while coping with stress does not affect employee engagement. Limitations: This study focuses on coping stress, social skills, internet addiction, and employee engagement, and only on millennial office workers in Jabodetabek. This is supported by very clear references on coping stress, social skills, internet addiction, and employee engagement Contribution: This research shows how to overcome stress, social skills, and internet addiction that affect employee engagement and shows employee engagement, stress coping, social skills, and internet addiction. This research will help companies to find ways to increase employee engagement in their companies.